A nomogram to predict the risk of sarcopenia in older people. Issue 16 (21st April 2023) - Yin, Guangjiao; Qin, Juanjuan; Wang, Ziwei; Lv, Fang; Ye, Xujun
Abstract : The burden of sarcopenia is increasing worldwide. However, most cases of sarcopenia are undiagnosed due to the lack of simple screening tools. This study aimed to develop and validate an individualized and simple nomogram for predicting sarcopenia in older adults. A total of 180 medical examination populations aged ≥60 years were enrolled in this study. Sarcopenia was diagnosed according to the Asian Working Group for Sarcopenia 2019 consensus. The primary data were randomly divided into training and validation sets. Univariate logistic regression analysis was performed to select the risk factors of sarcopenia, which were subjected to the least absolute shrinkage and selection operator for feature selection. A nomogram was established using multivariate logistic regression analysis by incorporating the features selected in the least absolute shrinkage and selection operator regression model. The discrimination and calibration of the predictive model were verified by the concordance index, receiver operating characteristic curve, and calibration curve. In this study, 55 cases of sarcopenia were available. Risk predictors included age, albumin, blood urea nitrogen, grip strength, and calf circumference. The model had good discrimination and calibration capabilities. concordance index was 0.92 (95% confidence interval: 0.84–1.00), and the area under the receiver operating characteristic curve was 0.92 (95% confidence interval: 0.83–1.00) in the validation set. The Hosmer-Lemeshow test had a P value of .94. The predictive model in this study will be a clinically useful tool for predicting the risk of sarcopenia, and it will facilitate earlier detection and therapeutic intervention for sarcopenia.